Correction to: Improving health promotion through central rating of interventions: the need for Responsive Guidance - Maarten Olivier Kok; Roland Bal; Caspar David Roelofs; Albertine Jantine Schuit (BMC, 2018)
Correction It has been highlighted that the original manuscript [1] contains a typesetting error in the surname of Caspar David Roelofs. This was incorrectly captured as Caspar David Roelefs in the original manuscript which has since been updated.